Procedural Aspects of Cybercrime Investigation - DRĂGAN, Alin Teodorus (Journal of Legal Studies, 2015)
Romanian legislation has had to adapt to new challenges. Following the ratification by our country of the provisions of the Council of Europe on cybercrime, in addition to substantive law provisions, procedural provisions have been introduced, which are intended to regulate the activity of criminal investigation bodies in investigating cybercrime offences.